(untitled) (Revista Rupturas, 2024)
Due to the urgency of political policies of defamiliarization and their financing, this research intends to add theoretical aspects to demonstrate the pertinence of reviewing the tax exemptions of the Free Trade Zones (FTZ) in Costa Rica, according to the duty of care of the companies affiliated to the FTZ scheme, by using qualitative methodology, documental revision strategy, and theoretical and exploratory approach. Therefore, it will demonstrate the need to review the FTZ scheme, in order to strengthen the defamiliarization care processes in Costa Rican society and contribute to improving women’s working conditions and opportunities.